Foodomics evaluation of the anti-proliferative potential of Passiflora mollissima seeds (2020)
The anti-proliferative potential of Passiflora mollissima seeds, an underexplored agri-food waste, was investigated in this work by evaluating the molecular changes induced at transcript and metabolite expression levels on HT-29 human colon cancer cells. For this purpose, a pressurized-liquid extract from P. mollissima seeds obtained under optimized conditions was used for the treatment of HT-29 cells and a multi-omics strategy applied, integrating transcriptomics and metabolomics analysis, along with viability and cell cycle assays to study the molecular mechanisms that explain the anti-proliferative activity of this fruit by-product. After treatment for 48 and 72 h, the viability of HT-29 colon cancer cells was markedly affected, whereas minor effects were observed on normal human colon fibroblast cells. The bioactive extract was shown to arrest HT-29 cells in the S and G2/M phases of the cell cycle, which might be mediated by the inactivation of the FAT10 cancer signalling pathway among other genes identified as altered in the transcriptomic analysis. In addition, cellular redox homeostasis, as well as the polyamines pathway and methionine metabolism were found to be affected as suggested from the metabolomics data. Finally, the Foodomics integration enabled the identification of genes, such as MAD2L1, involved in the polyamine and glutathione metabolism, or the inactivation of the NUPR1 transcription factor, that might be related with the alteration of the intracellular ceramide levels in response to endoplasmic reticulum stress.